2011
DOI: 10.4028/www.scientific.net/amr.374-377.590
|View full text |Cite
|
Sign up to set email alerts
|

Study on Treatment of Wastewater from the Production of PolyTHF with Extraction-Adsorption Method

Abstract: The wastewater from the production of polytetrahydrofuran (PolyTHF) was treated with union between of the extraction method and adsorption method. The results showed that using chloroform as extraction agent, CODCr removal rate could reach as high as 75%, then the treatment of wastewater was treated by adsorption method, which meet the national level of discharging standard, CODCr removal could reach at 100mg/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The time to reach equilibrium was between 2-3 hrs for GACC, whereas for GACP it was at the third hour. Bian et al (2011) found the similar results. Thus, the kinetics of adsorption is affected quickly (up to 1 hr).…”
Section: Cod Removalsupporting
confidence: 70%
“…The time to reach equilibrium was between 2-3 hrs for GACC, whereas for GACP it was at the third hour. Bian et al (2011) found the similar results. Thus, the kinetics of adsorption is affected quickly (up to 1 hr).…”
Section: Cod Removalsupporting
confidence: 70%